Guns N'Roses - Bateman B. (London Orion Books, 1994)
The most controversial rock band of the last decade, Guns N'Roses began their career with a 20 millionselling album, APPETITE FOR DESTRUCTION. Since then they;ve been through nline-up changes newsmaking concerts, busts and of course, great music.